Digital Technologies for Mathematics Learning in Rural Higher Education: Students’ Perspectives - Gqoli, Neliswa (Research in Social Sciences and Technology- OpenED Network, 2024)
The use of digital technologies is a fundamental part of being a university student. Hence, there is a growing interest in equipping students with the skills they need to thrive in a world that is full of technology and constantly changing. Moreover, the need to provide university students with the skills they need to succeed in a rapidly changing, technologically advanced society is also growing. It has become more common for students to learn mathematics using digital technologies and conventional techniques as a result of recent advancements in both the world and technology. To ensure the future of mathematics students and society for sustainability, technology, and education should collaborate. The study investigated how students felt about using digital technology to teach mathematics. This study employed a case study design and was qualitative in nature. The technology Acceptance Model was employed as the theoretical framework which explains how to encourage users to accept and utilise new digital technologies. Twenty second-year mathematics students who were specifically chosen to be information-rich participants made up the study's participant pool. Data were collected using semi-structured interviews. The collected data was analysed using thematic analysis. The findings revealed that students had a positive attitude towards embracing digital tools to learn mathematics. However, they encountered some difficulties as they were learning mathematics using digital tools.